Sleep characteristics and cardiometabolic disease risk factors in corporate executives - Pienaar, Paula (Department of Human Biology, 2024)
Hours spent in work and sleep comprise the majority of time in a typical day of working adults. As a result, the workplace is a key setting for public health action. Among working adults, 71% of deaths globally are related to non-communicable diseases (NCDs), most of which are attributed to cardiometabolic diseases (CMD). While there is clear evidence linking short sleep duration with CMD risk in the general population, similar data in a unique subset of the workforce, namely corporate executives, remains largely unexplored. The purpose of this thesis was to investigate the associations between sleep health and CMD risk in corporate executives. A systematic review and meta-analysis examined associations between selfreported sleep duration, all-cause mortality (ACM) and cardiovascular disease mortality (CVDM) in employed adults. Sleeping